3D seismic structure of the Zhenbei–Huangyan seamounts chain in the East Sub‐basin of the South China Sea and its mechanism of formation. (18th February 2016) - Wang, Jian; Zhao, Minghui; Qiu, Xuelin; Sibuet, Jean‐Claude; He, Enyuan; Zhang, Jiazheng; Tao, Chunhui
Abstract: The probable N055°‐oriented extinct spreading ridge of the East Sub‐basin is cut across by the post‐spreading volcanic ridge oriented approximately E–W in its western part and called the Zhenbei–Huangyan seamounts chain. A three‐dimensional ocean bottom seismometer survey was conducted in 2011 and covered both the extinct spreading ridge and the Zhenbei–Huangyan seamounts chain in the East Sub‐basin. The comprehensive seismic record sections of 39 ocean bottom seismometers underline the high‐quality data with clear and reliable P ‐wave seismic first arrivals. The three‐dimensional tomographic results show that the crust is oceanic on each side of the Zhenbei–Huangyan seamounts chain. The seafloor spreading lineaments and associated fracture zones pattern provide channels for magma migration and eruption. Based on the ratio of volcanic extrusive and intrusive materials and the shape of the upward convex 6.4 km/s iso‐velocity curve beneath the Zhenbei and Huangyan seamounts, we conclude that the Zhenbei and Huangyan seamounts appear to be dominantly formed by intra‐crustal intrusion. Combining previous geochemical studies of post‐spreading volcanic ridge outcropping samples, the formation mechanism of the seamounts chain might be explained by a buoyancy‐driven decompression melting mechanism occurring as separately evolving partial melting bodies beneath each seamount. Copyright © 2016 John Wiley & Sons, Ltd.